Tree‐ring‐based annual precipitation reconstruction for the Hexi Corridor, NW China: consequences for climate history on and beyond the mid‐latitude Asian continent. (12th April 2013) - Chen, Feng; Yuan, Yujiang; Wei, Wenshou; Zhang, Ruibo; Yu, Shulong; Shang, Huaming; Zhang, Tongwen; Qin, Li; Wang, Huiqing; Chen, Fahu
<x xml:space="preserve">Abstract</x> An annual (July to June) precipitation reconstruction for the period AD 1760–2010 was developed from a Picea crassifolia regional tree‐ring chronology from two sites in the northern mountainous region of the Hexi Corridor, NW China. This reconstruction explains 52.1% of the actual precipitation variance during the period 1951 to 2010. Spatial correlations with gridded land‐surface data reveal that our reconstruction contains a strong regional precipitation signal for the Hexi Corridor and for the southern margin of the Badain Jaran Desert. Significant spectral peaks were identified at 31.9, 11.1, 8.0, 7.0, 3.2, 2.6 and 2.2 years. A large‐scale comparison indicates that our reconstruction is more consistent with climate records of a Westerly‐dominated Central Asia, and that the Westerlies have a greater impact on the precipitation in this region than the Asian summer monsoon. Our reconstructed precipitation series is significantly correlated with sea‐surface temperature (SST) in the tropical Atlantic Ocean (positive), the tropical Indian Ocean (positive), the western tropical Pacific Ocean (positive), and the western North Pacific Ocean (negative). The spatial correlation patterns between our precipitation reconstruction and SSTs of the Atlantic and Pacific Oceans suggest a connection between regional precipitation variations and the high‐mid‐latitude northern atmospheric circulations (Westerlies and Asian summer monsoon).